ALTYAZI ÇEVİRİSİNDE BİR KISITLAMA: SENKRON - (:unkn) unknown (My University, 2017)
Son yıllarda çeviribilim kapsamında değerlendirilmeye başlanmış olan görsel-işitsel çeviri çalışmaları, bu alandaki ürünlerin niteliğinin artmasına katkıda bulunmaktadır. Görsel-işitsel çeviri üst kavramı altında öne çıkan en yaygın görsel-işitsel çeviri yöntemleri dublaj ve altyazıdır. Dublaj, altyazıya göre daha zahmetli ve masraflı bir süreçtir ve dublaj izleyicisi ayrıdır. Ülkemizde sinemada gösterime giren yabancı filmler genellikle altyazı yöntemiyle izleyiciye sunulmaktadır. Altyazı, en genel anlamda yabancı bir izlentide yer alan işitsellerin ve izleyici açısından çeviri gerektiren diğer göstergelerin erek dile yazı kanalıyla çevrilmesidir. Erek dile çevirisi yapılmış altyazı ekranın genellikle alt bölümünde yer alır. Ekranın altında en fazla iki satır olacak biçimde yer alan altyazının, orijinali/özgün içeriği ile aynı içeriğe sahip olması beklenir. Bunun için yer ve zaman sıkıntısından dolayı kimi zaman erek metinde kısıtlamaya gidilir. Bu çeviri yönteminde en önemli noktalardan birisi, ekrana gelen altyazıların izlentideki diyalog ve görüntülerle eşzamanlı/senkronize olmasıdır. Bu çalışmada görsel-işitsel ürünlerin çevirisinde kullanılan altyazıya ilişkin kuramsal bilgilere yer verildikten sonra, altyazı çevirisinde dikkat edilmesi gereken noktalar arasında önemli bir yeri olan senkrona yönelik çeviri sorunları ele alınmıştır. Araştırmada, altyazı sürecinde görsel ve işitsel açıdan senkronun önemi ve gerekliliği, altyazıda senkron sorununun kaynağı, senkronun çeviri sürecini nasıl yönlendirdiği ve çeviri ürününün niteliğini nasıl etkilediği ortaya konulmaya çalışılmıştır.

Over the last few years, the advent of the evaluation of audio-visual translation methods within the context of translation studies in the field has played a role in increasing the quality of products. The most common audio-visual translation methods under the generic term of the audiovisual translation are dubbing and subtitling. Dubbing is more costly and arduous in comparison with subtitling. The viewer of dubbed films should be considered apart from the view of subtitled films. The foreign movies coming out in our country are usually subtitled for viewers. Subtitling as a translation method can be evaluated in the general sense as the written translation of verbal and non-verbal signs of an audio-visual product that are meaningful from the perspective of the viewer and need to be translated. The translation of film dialogues into the target language as written lines generally appears at the bottom of the screen. It is anticipated that the subtitles appear at the most as two sentences at the bottom of the screen that the content is the same as the original and that it has the same effect on the viewer as the original. In order to ensure this, the subtitles have to be reduced usually due to time and space constraints. The most important point in audio-visual translation method is the synchrony between the audio-visual signs of the film and the content of the subtitles. This study has examined the theoretical information used in relation to subtitle translation of films and TV programmes and has then considered the points that should be taken into account with regard to subtitle translation. Within this context, issues relating to synchrony, which play an important role in relation to subtitle translation, were also examined. The research carried out has attempted to highlight the importance and necessity of synchrony from a visual and audio perspective, the root of synchron issues, how synchrony affects the translation process and the quality of the translation product.
SYNCHRONY: A CONSTRAINT IN SUBTITLING